Stimulation Application Training for Early Intervention Detection of Child Development for Teachers at TK Sejahtera 4 Tasikmalaya City - Winda Windiyani; Sri Wahyuni; Sri Susilawati; Jihan (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Stimulation, early detection and early intervention is an effort to prevent developmental deviations in a comprehensive and coordinated manner that can be held in the form of partnerships between families (parents, child caretakers and other family members), the community (cadres, community leaders, professional organizations, non-governmental organizations) and professionals (health, education and social). PAUD and Kindergarten teachers have a role, one of which is an indirect target in the implementation of SDIDTK so that it is expected to help improve the quality of early childhood growth and development and readiness to enter formal education. The goal in the form of a community partnership program is to teach kindergarten teachers to use the SDIDTK application to make it easier to monitor children's growth and development. The method used is by training teachers about the SDIDTK application and then providing assistance when monitoring children's growth and development The expected outcome after conducting SDIDTK training for teachers using the SDIDTK application is that teachers will be skilled at monitoring child development. Conclusion This application can be useful for teachers in carrying out monitoring of children's growth and development.